Federal Funds for Community Education: A Mixed Blessing - Clyde LeTarte (Educational Considerations, 1974)
The quest for quality leaders in great quantities could be the nemesis of the community education program. The injection of large doses of federal funds demands serious planning for the training of future community educators.